2007
DOI: 10.1200/jco.2007.25.18_suppl.7042
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system (CNS) leukemia after imatinib mesylate therapy for chronic myelogenous leukemia (CML)

Abstract: 7042 Background: Imatinib is the standard first line treatment for CML. Imatinib penetrates the CSF poorly. We examined the incidence and outcome of CNS disease in pts with CML treated with imatinib at our institution. Methods: The clinical data for pts with early or late chronic phase and accelerated phase CML treated with imatinib between 1999 and 2006 were reviewed. Pts who were started on imatinib elsewhere and progressed to blast phase were also included. CNS disease was defined as a pathologically prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Blastic phase of CML is not limited to peripheral involvement. In a review made by Sohl of 900 patients with CML being treated with Imatinib, they identified 30 patients with extramedullary involvement 15 of which is CNS [6]. Since 1980's reports regarding incidence of CML with extramedullary involvement were documented, most commonly affecting the lymph nodes and a rather small group involving the CNS [7].…”
Section: Discussionmentioning
confidence: 99%
“…Blastic phase of CML is not limited to peripheral involvement. In a review made by Sohl of 900 patients with CML being treated with Imatinib, they identified 30 patients with extramedullary involvement 15 of which is CNS [6]. Since 1980's reports regarding incidence of CML with extramedullary involvement were documented, most commonly affecting the lymph nodes and a rather small group involving the CNS [7].…”
Section: Discussionmentioning
confidence: 99%